Strengthening Local Economic Growth Through Community Purchasing of Local Food Products: A Qualitative Study in Barru Regency - Alwi, Muchdi (International Journal Of Education, Social Studies, And Management (IJESSM), 2026)
This study aims to analyze the role of community purchasing behavior toward local food products in strengthening local economic growth in Barru Regency. The research adopts a qualitative approach to gain an in-depth understanding of the economic motivations, preferences, and consumption patterns of the community. Data were collected through in-depth interviews, observations, and documentation involving local consumers, small-scale producers, and relevant stakeholders. The data were analyzed using NVivo software to identify key themes and patterns related to purchasing behavior and its economic implications. The findings reveal that community purchasing of local food products is influenced by several economic factors, including price affordability, product accessibility, income level, and perceived value. In addition, non-economic factors such as cultural attachment, product trust, and local identity also play a significant role in shaping consumer decisions. The study further indicates that increased consumption of local food products contributes to strengthening local economic circulation, supporting small and medium enterprises (SMEs), and creating sustainable income opportunities for local producers. This research highlights the importance of integrating economic and socio-cultural strategies to encourage community participation in supporting local products. Policy recommendations include strengthening local product competitiveness, improving distribution channels, and enhancing public awareness to promote sustainable local economic development in Barru Regency.